Effectiveness of Carvedilol versus Indapamide in Uncontrolled Diabetic Hypertensive Patients being Treated with Olmesartan and Amlodipine (Medicine Today, 2018)
Hypertension is the commonest preventable cause of death among the diabetic patient. Current guidelines recommend using combination drug therapy in case of uncontrolled hypertension in diabetic patient. Even though, duel combinations are sometimes insufficient to achieve target blood pressure. Objective of this study was to evaluate the efficacy and safety of Indapamide and Carvedilol as third drug in controlling hypertension in diabetic patients. This prospective comparative study was conducted in 32 well controlled diabetic patient with uncontrolled hypertension those who taking Olmesartan (20 mg/day) and Amlodipine (5 mg/day). Addition of both the drugs showed significant reduction of all the blood pressure parameters at the end of six weeks therapy without any major adverse effects. Systolic blood pressure decreased from 169.71±9.26 to 119.41±12.48 in Indapamide group (p